Consideration for effective height of sea walls against tsunami. Issue 4 (2nd April 2016) - Kanda, Jun
Abstract : Tsunami wave height data at several sites in Tohoku district in Japan were examined and an empirical extreme value distribution with both upper and lower bounds was applied to model the cumulative probability distribution function of annual maximum wave height. Then by estimating the construction cost of sea walls against the tsunami and the expected damage cost due to a tsunami attack, the expected total cost was studied. Observation of the tendency of expected total cost with the design height of a sea wall indicates that sea wall construction is not economically justified, unless the height exceeds the upper bound of tsunami wave height.